FIRST STEPS – a randomized controlled trial on the evaluation of the implementation and effectiveness of two early prevention programs for promoting the social integration and a healthy development of children with an immigrant background from 0–3. Issue 1 (December 2015) - Lebiger-Vogel, Judith; Rickmeyer, Constanze; Busse, Annette; Fritzemeyer, Korinna; Rüger, Bernhard; Leuzinger-Bohleber, Marianne
Abstract Background The social integration of children with an immigrant background has become one of the most urgent social responsibilities in Germany. They are more likely to live in high-risk environments and are disadvantaged with respect to health related variables as well as educationally. Quite a number of projects supporting their integration into the German society exist although many are hardly scientifically evaluated. Most of them focus on the acquisition of German language and therefore address older children (and adults). However, international experts agree that social integration is not only a matter of language but also of earlier developmental processes of children in their first months of life connected to adequate early parenting. Methods/Design The model project FIRST STEPS focuses on earliest prevention for children with an immigrant background, supporting their parents in the critical phase of migration and early parenthood. In a prospective randomized comparison group design the effectiveness of a psychoanalytically oriented early prevention program (intervention A) is compared to the outcomes of groups offered by paraprofessionals with an immigrant background (intervention B). Intervention A is a professional offer supporting immigrant families based on developmental psychological and on knowledge on early parenting. 180 families are randomly assigned to intervention A or B. They are supported during the first 3 years of the children's lives. Social and family stressors, the quality of the parent–child-interaction, child attachment security, the affective, cognitive and social-emotional development of the children and the social integration of the families are assessed during and after the intervention. Discussion The project aims at evaluating the implementation as well as the short- and long-term effectiveness of psychoanalytically oriented intervention A compared to the outcomes of intervention B. It is expected that professionally supported early parenting (intervention A) improves the social-emotional, cognitive and language development of immigrant children as well as the social integration of their families to a greater extent than in the comparison groups. In case the model project proves to be effective, a rollout across Germany is possible. Due to the "difficult-to-reach" immigrant families challenges in recruitment, uptake and retention of participants are anticipated. Trial registration DRKS-ID:DRKS00004632, trial registration date: 05.02.2013